Men at arms : a novel of discworld - Pratchett, Terry (Harper, an imprint of HarperCollinsPublishers, 2013)
"Corporal Carrot has been promoted. He's now in charge of the new recruits guarding Ankh-Morpork, Discworld's greatest city, from Barbarian Tribes, Miscellaneous Marauders, unlicensed Thieves, and such. It's a big job, particularly for an adopted dwarf. But an even bigger job awaits. An ancient document has just revealed that Ankh-Morpork, ruled for decades by Disorganized crime, has a secret sovereign. And his name is Carrot"--Page 4 of cover.